FOREIGN BODY REMOVAL VIA TRACHEOSTOMY. AN UNCOMMON OCCURRENCE: Foreign Body Removal Via Tracheostomy - Butt, Dr Kamran Ashfaq Ahmed; Hassan, Zaheer Ul; Khan, Maryam; Akram, Chaudhry Muhammad Bilal (Pakistan Armed Forces Medical Journal, 2018)
Foreign body airway in a trauma patient is a relatively common occurrence however rigid and flexible bronchoscopy remains the modality of choice for removal of foreign bodies. We present a case of foreign body air way following an RTA which was unsuccessfully removed via a non conventional technique.